Addressing the policy cacophony does not require more evidence: an argument for reframing obesity as caloric overconsumption - Shelley Jacob J (BMC, 2012)
Abstract Background Numerous policies have been proposed to address the public health problem of obesity, resulting in a policy cacophony. The noise of so many policy options renders it difficult for policymakers to determine which policies warrant implementation. This has resulted in calls for more and better evidence to support obesity policy. However, it is not clear that evidence is the solution. This paper argues that to address the policy cacophony it is necessary to rethink the problem of obesity, and more specifically, how the problem of obesity is framed. This paper argues that the frame "obesity" be replaced by the frame "caloric overconsumption", concluding that the frame caloric overconsumption can overcome the obesity policy cacophony. Discussion Frames are important because they influence public policy. Understood as packages that define issues, frames influence how best to approach a problem. Consequently, debates over public policy are considered battles over framing, with small shifts in how an issue is framed resulting in significant changes to the policy environment. This paper presents a rationale for reframing the problem of obesity as caloric overconsumption. The frame "obesity" contributes to the policy cacophony by including policies aimed at both energy output and energy input. However, research increasingly demonstrates that energy input is the primary cause of obesity, and that increases in energy input are largely attributable to the food environment. By focusing on policies that aim to prevent increases in energy input, the frame caloric overconsumption will reduce the noise of the obesity policy cacophony. While the proposed frame will face some challenges, particularly industry opposition, policies aimed at preventing caloric overconsumption have a clearer focus, and can be more politically palatable if caloric overconsumption is seen as an involuntary risk resulting from the food environment. Summary The paper concludes that policymakers will be able to make better sense of the obesity policy cacophony if the problem of obesity is reframed as caloric overconsumption. By focusing on a specific cause of obesity, energy input, the frame caloric overconsumption allows policymakers to focus on the most promising obesity prevention policies.